PENGARUH SEBARAN GENERASI TERHADAP MOTIVASI KERJA DI INDUSTRI PERBANKAN AREA TANAH ABANG - Shinta Winasis (Universitas Mercu Buana, 2018)
Generation Gap, is an issue that in the past few years has become one of many concern of human resource managers. The generation gap will cause frictions among employees, jeopardize teamwork spirit and, at the end, cause unsatisfied organizational performance. According to the researcher's view, the gap and miscommunication occurred are generally caused by differences in point of view, motivation and work ethic. Based on this phenomenon, in this research we will study the motivation of work of each generation in Private Bank Branch Office XYZ located in the trading area Tanah Abang. Literature review from various scientific papers will be used to explain this topic. The results of this study are expected to provide input for determining the management of human resource policies related to generation gap